The long arc of legality : Hobbes, Kelsen, Hart - Dyzenhaus, David (Cambridge : Cambridge University Press, 2022)
The Long Arc of Legality breaks the current deadlock in philosophy of law between legal positivism and natural law by showing that any understanding of law as a matter of authority must account for the interaction of enacted law with fundamental principles of legality. This interaction conditions law's content so that officials have the moral resources to answer the legal subject's question, 'But, how can that be law for me?' David Dyzenhaus brings Thomas Hobbes and Hans Kelsen into a dialogue with H. L. A. Hart, showing that philosophy of law must work with the idea of legitimate authority and its basis in the social contract. He argues that the legality of international law and constitutional law are integral to the main tasks of philosophy of law, and that legal theory must attend both to the politics of legal space and to the way in which law provides us with a 'public conscience'.
Introduction -- The Puzzle of Very Unjust Law I: Hart and Dworkin -- The Puzzle of Very Unjust Law II: Hobbes -- The Constitution of Legal Authority : The Authority of Legal Constitutions -- The Janus-Faced Constitution -- The Politics of Legal Space -- Legality's Promise -- Appendix I. Exclusive and Inclusive Legal Positivism -- Appendix II. Kantian Private Law Theory -- Appendix III. John Finnis and 'Schmittean Logic'.
Title from publisher's bibliographic system (viewed on 13 Jan 2022).
Keywords: Rule of law -- Philosophy; Law -- Philosophy